Service quality and customer satisfaction : antecedents of customer's re-patronage intentions - Yap, Sheau Fen; Kew, Mew Lian (Sunway University College, 2007)
This study was designed to examine the relationship between service quality, customer satisfaction and customer?s re-patronage intentions in the context of the restaurant industry. The respondents were 377 restaurant patrons who completed the self-administered questionnaire. Pearson Correlation analysis indicated that service quality and customer satisfaction had a direct positive effect on customer?s re-patronage intentions. Multiple Linear Regression highlighted customer satisfaction as a stronger predictor of re-patronage intentions compared to service quality. Possible interpretations, limitations, and implications for marketing professionals are discussed.